Evaluation of mandibular implant sites: correlation between panoramic and linear tomography - Rockenbach Maria Ivete Bolzan; Sampaio Maria Carméli Correia; Costa Lino João da; Costa Nilza Pereira da (Fundação Odontológica de Ribeirão Preto, 2003)
The reliability of the linear tomography and panoramic radiography made with X-ray equipment was evaluated (Vera View Scope X-600; Morita). The sample was composed of 20 dry human hemimandibles, in which the area selected for analysis was 1.5 cm distal from the limit set before the mental foramen. Four measurements were made. The images obtained were drawn on acetate paper and the hemimandibles cut at the demarcated area. The measurements were made using a digital electronic pachymeter. The values found for the radiographic images were compared to those obtained in the mandibular specimens and submitted to statistical evaluation by the Wilcoxon test. It was concluded that both techniques were reliable for the accomplishment of vertical linear measurements in the selected area. However, a 2.0 mm safety margin is recommended.